2021
DOI: 10.1155/2021/6696779
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Virtual Reality and Computer Game-Based Cognitive Therapy on the Development of Visual-Motor Integration in Children with Intellectual Disabilities: A Pilot Study

Abstract: Purpose. Visual-motor integration is a good indicator of a child’s overall developmental and functional level. This study investigated the combined effects of virtual reality (VR) and computer game-based cognitive therapy on the development of visual-motor integration in children with intellectual disabilities. Methods. The study used a single-group pre-post study design and 13 children with intellectual disabilities who were recruited from a community rehabilitation center participated in the study. We used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…This result is inconsistent with previous studies showing the efficacy of VRR compared to regular exercise for motor performance and strength outcomes in different conditions, such as cerebral palsy, senility, and after stroke [65][66][67]. One study found VRR effective for the treatment of cognitive impairment in cancer survivors, consistent with the previous literature stating the efficacy of VRR interventions for cognitive impairment [68][69][70][71][72].…”
Section: Discussioncontrasting
confidence: 72%
“…This result is inconsistent with previous studies showing the efficacy of VRR compared to regular exercise for motor performance and strength outcomes in different conditions, such as cerebral palsy, senility, and after stroke [65][66][67]. One study found VRR effective for the treatment of cognitive impairment in cancer survivors, consistent with the previous literature stating the efficacy of VRR interventions for cognitive impairment [68][69][70][71][72].…”
Section: Discussioncontrasting
confidence: 72%
“…Studies on children without disabilities and with intellectual disabilities have also confirmed that game-based cognitive training can provide meaningful improvements in the cognitive abilities, working memory, and perceptual reasoning skills; it has also been confirmed that such training is suitable for online contents, which are generally easy to use [32]. Game-based cognitive training has been confirmed to be appropriate for children with intellectual disabilities, and VR and computer game-based cognitive training have also been shown to improve visual perception and behavioral functions in these children [33]. The possibility of game-based cognitive training as a cognitive rehabilitation tool was confirmed by verifying significant differences before and after intervention of game-based cognitive training programs through analysis of Mini-Mental State Examination (MMSE) [34].…”
Section: Introductionmentioning
confidence: 70%
“…The Wechsler Intelligence Scale was used to measure the intelligence quotient (IQ) of the participants ( Jamile Benite Palma Lopes et al, 2017 ). The inclusion criteria ( Eid, 2015 ; Lee et al, 2016 ; Ahn, 2021 ) were: 1) adolescents whose IQ ranged from 50 to 70; 2) adolescents who can follow the therapist’s commands; and 3) adolescents who can independently stand and walk. The exclusion criteria ( Cowley et al, 2011 ; Lee et al, 2016 ; Ahn, 2021 ) were: 1) any contraindications to exercise; 2) severe intellectual, visual and hearing disability; and 3) any musculoskeletal, neurological, cardiovascular or respiratory system disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies showed the effect of VR training on balance and lower extremity muscle strength in adolescents with ID. In previous studies, VR has been used to improve the functional abilities of individuals with ID ( Patrice L Tamar Weiss et al, 2003 ; Shira Yalon-Chamovitz and Weiss, 2008 ; Lotan et al, 2009 ; Ahn, 2021 ). Shira et al showed that VR appeared to offer diverse and stimulating experiences during leisure activities among individuals with ID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation